Design of dual peak star shaped metamaterial absorber for S and C band sensing applications - Muhammad Amir Khalil; Wong Hin Yong; Md. Shabiul Islam; Lo Yew Chiong; Ahasanul Hoque; Najeeb Ullah; Hui Hwang GOH; Tonni Agustiono KURNIAWAN; Mohamed S. Soliman; Mohammad Tariqul Islam (Scientific Reports)
Abstract This paper presents the detailed design configuration and investigation of a small-scale dual-band metamaterial absorber (MTMA) for solid and liquid sensing applications. The overall dimension of the MTMA unit cell is 10 × 10 × 1.57 mm3 and constitutes an affordable FR-4 substrate. The absorber exhibits dual absorption peaks at 3.470 GHz for the S-band and 7.219 GHz for the C-band, respectively. Both absorption characteristics have been validated through comprehensive simulation and experimental procedures. The dual-band absorption rate exceeded 99% during simulations, and experimental validation showed an absorption rate above 98%. For sensing applications, various solid materials, including different Rogers substrates ( RT 5880, RT 5870, RT 4003 and RT 4835) and liquids such as sunflower and crown oil, were utilized. Our findings indicate that the proposed MTMA achieves a maximum Q-factor of 191 and a sensitivity of up to 2.5 for both solid and liquid sensing applications compared to previous studies. The simulation and experimental validation of the result indicate that suggested MTMA can be effectively used in different sensing applications such as the medical and communications industry.